THE ISLAMIC MOVEMENT OF UZBEKISTAN AS A SECURITY THREAT OF CENTRAL ASIA COUNTRIES - Целуйко, М.Є. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The article reveals the activities of the terrorist organization Islamic Movement of Uzbekistan since the beginning of its existence to the modern period. The ideological and organizational dynamics of the organization development, the degree and directions of its activity, the types and importance of external relations at different stages of the IMU existence are estimated. Assumptions about the prospects for future activities of the Islamic Movement of Uzbekistan are made.